Evaluación energética de la UEB vinos Bayamo - Corrales Tapia, Carlos Ramiro (2016)
The present work was developed in the UEB wine of Bayamo city, the same one had for general objective to evaluate the level of energy administration in the company. This is guided to the development of the Energy Administration in the Companies of high consumption of conventional energy payees. Firstly we decided to carry out a diagnosis by the whole installation where they took the approaches for the evaluation and integral diagnosis of the production system. After that we used the Technology of Total Management of Energy.